Toxic Masculinity in Africa and the Bible: The Strong-man Model and the Co-optation of Feminist Biblical Interpretation - Wafawanaka, Robert (Old Testament Essays, 2022)
The present article discusses the concept of toxic masculinity in the context of African political history, leadership models and feminist biblical interpretation. It explores and problematises the idea of manliness as a key concept of masculinity exhibited in the African context by warrior queens and perpetuated by modern African leaders. The essay will demonstrate that such masculinity is toxic and it uses this backdrop to investigate how feminist biblical scholarship interpret the portrayal of women characters in the Bible. This approach uncovers a tendency by feminist scholars to interpret some biblical women characters (such as Sarah, Hagar, Yael, Rahab, Jezebel, and Abigail) in a toxic way—as strong men, or even better men. As a result, feminist scholarship unwittingly contributes to toxic masculinity by presenting women who outdo men. The goal of this article is to expose the potential for co-optation of feminist biblical interpretation by toxic masculinity. This observation leads to an alternative and contextual reading of women characters in the Bible in a non-toxic way that potentially rehabilitates them. The ramifications of reading biblical women in a non-toxic way have potential implications for reading biblical men in a non-strong-man and non-toxic way. https://doi.org/10.17159/2312-3621/2021/v34n3a9